.Effect of planting technique and water stress on vegetative growth of Zea mays L - Issa, Sajid Hamid; Al - Mubarak, Nader Falih Ali; Al - Anbari, Asil Kazem Mahdi (Journal of agricultural, environmental and veterinary sciences, 2018)
A field experiment was carried out at the experiment field of department of field crops sciences. Baghdad variety during 2017 spring season is new Baghdad plant nursery in Diyala directorate of agriculture in Diyala province. According to the split plots design with three replications. The water quantity(8400m3/h) was occupied the main plots while agriculture technique methods (plastic , cork , prose and conventional) was occupied the sub plots seedling were transferred to the permanent field in 15/3/2017.Seedling were transferred to the permanent field in 15/3/2017 when seedling were to 5 leaves after 30 days from planting and seed planting of conventional agriculture method in the permanent field in same date of seedling agriculture. Results have shown that water quantity (8400m3/h) gave best average results in single leaf area , leaf area index and the conventional agriculture gave the highest average in number terrestrial papers. There was a significant overlap between the treatment of water stress and the methods of agriculture in all the character under study. The synthesis of water quantity (8400m3/h) to agriculture with plastic dishes was given highest average in the number of total leaves and number of green leaves and single leaf area and leaf area index. While the synthesis of quantity water (8400m3/h) for conventional agriculture was given the highest average in number terrestrial leaves.